Pembiayaan Pasien Skizofrenia Paranoid - Mahanggi, Oktarina; Rahem, Abdul; Nita, Yunita (Journal of Telenursing (JOTING), 2023)
This study aims to determine the burden of direct medical costs on paranoid patients at Tombulilato Regional Hospital and the factors influencing direct medical costs. The method used in this research was retrospective, using medical record data and details of direct medical costs. The results of this research are that the total direct medical costs of inpatient schizophrenia patients are IDR. 523,028,500, with the most significant accommodation cost being the room cost of Rp. 184,190,000 because the patient's length of stay is very strongly related to direct medical costs. The conclusion is that the total direct medical costs incurred amounted to Rp. 523,028,500 with the relationship between the length of hospital stay and direct medical expenses. Keywords: Direct medical costs, influencing factors, schizophrenia